Investigating the Symmetric and Asymmetric Impacts of Oil Price Fluctuations on Green Energy Transition in Oil-Exporting and Oil-Importing Countries - Soltani, Hassen (International Journal of Energy Economics and Policy, 2025)
This research explores the repercussions of oil price on green energy transition across a panel of oil-exporting and oil-importing nations between 2000 and 2020. Employing a wide range of second-generation panel data techniques, specifically the PMG-ARDL framework, the research examines the symmetric and asymmetric repercussions of oil price, research and development expenditures, GDP, and GHG emissions on energy transition. The symmetric analysis indicates a positive connection between oil price and energy transition in the full sample and both sub-samples, with a stronger impact observed in oil-exporting nations. Furthermore, research and development expenditures, GHG emissions, and GDP positively influence green energy transition in the long-term. The asymmetric analysis reveals some new findings since it suggests that only oil price increases positively drive green energy transition in the long-run, while price decreases show no significant impact. This asymmetry holds across the full sample and both country groups. However, the positive influence of oil price increases on green energy transition is more apparent in oil-exporting nations. These findings carry significant policy implications for formulating targeted recommendations aimed at achieving a net-zero economy and promoting environmental sustainability.